Combining SLA Theory and Teaching Practice: “Big Bowl of Serial”, or, How to Use TV Series to Become Autonomous Learners of English - Anselmo, Anna; Refraschini, Elena (ALLiED, 2025)
This article deals with an asynchronous, fully online English course titled “Big Bowl of Serial”, which is analysed using Leo van Lier’s ecology of language learning framework (2004). The current scholarly interest in multimodal content and its uses and potential benefits in the classroom (Pattemore/Muñoz 2023) is fertile ground for critically presenting “Big Bowl of Serial” as a case study. The article introduces, firstly, the critical description of “Big Bowl of Serial” (its learning objectives, the theory at its core, and its structure), and, secondly, the analysis of its features in the light of Leo van Lier’s ecology of language learning and its four main constructs – relation, action, perception, and quality (2004). The article is divided into different sections accordingly: after a short introduction, there follows a descriptive section concerning the structure and aims of “Big Bowl of Serial”, after which, the course is analysed using van Lier’s framework (2004); the final section of the article sums up the strengths of the course that emerge from the analysis, and identifies areas that might be further developed in the future.